Dress for success: Factors effecting business success of Small Medium Enterprise (SMEs) : A case study in Kuala Terengganu / Fadhilahtul Liyana Abdul Manan - Abdul Manan, Fadhilahtul Liyana (Bachelor of Science (Hons.) Statistics, 2015)
SME Corporation Malaysia indirectly has played a big role in the Malaysia’s economy as government agencies support to the small medium enterprise (SMEs). SME Corporation Malaysia has deal with a lot of entrepreneurs to ensure the systematic process of the business. The purpose of the study is to examine the factors affecting the business success of Small Medium Enterprise (SMEs). The variables involved in this study are quality service, customer satisfaction, government support and social network towards variable SMEs success. The population of the study consisted of 150 SMEs who participate the seminar that obtained by SME Corporation Malaysia (Terengganu). The study utilized a random stratified sample to withdraw a representative sample. 150 questionnaire were distributed and (108) out of which were acceptable for Statistical Package for the Social Sciences (SPSS) to analyze the primary data collected. Reliability analysis were performed. The study revealed a number of findings most importantly: There is a statistical significant impact of quality service, customer satisfaction, government support and social network in the business success of Small Medium Enterprise (SMEs)